The role of peer inquiry communities in advancing technology integration for practitioners in adult basic education - Jennifer Kobrin (Adult Education Research Conference, 2020)
This paper explores how peer communities, one element of a larger collaborative, inquiry-based professional development project in adult education, advance participants’ knowledge and use of technology. As the designer and facilitator of the project, the author drew from memos and field notes, in addition to interviews and written reflections with 6 of 9 total participants who were teachers and administrators in Adult Basic Education programs. Findings indicate successful technology integration entailed participants combining their own experiences with established research to create “knowledge-of-practice” (Cochran-Smith & Lytle, 2009), and that knowledge generation within the peer communities reflected a horizontal trajectory.
Keywords: Technology integration; technology adoption; technology; adult education; adult basic education; communities of practice; practitioner inquiry; professional development